The land belongs to us... Or does it? - Semenya, Tsholofelo Gontse (My University, 2019)
Conversations in South Africa around land reform and decolonisation have been widespread, contested and debated for many years. The importance of returning land to its rightful former owners has become an integral part of reclaiming our country’s history and most importantly, framing its future. But what of the redistribution of land by traditional leaders who remain the custodians thereof in rural parts of South Africa? This research details the journey of a young woman and her family’s quest to reclaim rural land which, is said to have rightfully belonged to them - a land claim which was ultimately abandoned by my family. Neither myself nor the family members involved in the land claim grew up or lived in the area. Trying to reclaim a part of my family’s history and legacy was an emotional journey fraught with the struggles of reimagining my identity and understanding my family’s history, legacy and culture. This report details how the Semenya family found a home in the small, rural Limpopo town of Moletjie centuries ago. This report also details the symbolic understanding of what land and culture mean to my family today. The journey of my family’s abandoned land claim ties into present-day political narratives of land reform, the policies and custodians which inform its implementation and ultimately the reclaiming of black people’s history through land. Additionally this report will explore the historical and contemporary significance of land to black people in South Africa, as a means towards their economic development and cultural understanding of self.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework in Journalism and Media Studies, Faculty of Humanities, School of Literature, Language and Media, University of Witwatersrand, Johannesburg, 2019
Keywords: Pedi (African people); Rural-urban migration-South Africa